IMPLEMENTASI MODEL PEMBELAJARAN MATEMATIKA PENDIDIKAN SEKOLAH DASAR BERBASIS KEUNGGULAN LOKAL DI KABUPATEN ACEH TENGAH - Harahap, Rosliana; Lubis, Nur Ainun; Nurmalina, Nurmalina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Purpose of this study is to: to find out the objective conditions of local superiority in mathematics learning in elementary schools in Central Aceh Regency, to design mathematical learning models based on local superiority of class I students, and to find out student responses to local excellence based mathematics learning models in Central Aceh Regency. The subjects of this study were all 4th grade students of elementary school in Bebesen Central Aceh District. And the samples are SD 1 Bebesen, SDN 2 Bebesen, SDN 5 Bebesen, SDN 8 Bebesen, SDN 9 Bebesen, SD 10 Bebesen, SDN 10 Bebesen, SDN 11 Bebesen, SDN 12 Bebesen, SDN 14 Bebesen, SDN 16 Bebesen, SDN 16 Bebesen, SDN 17 Bebesen, SDN 17 Bebesen, SD IT Scholar. The research results were obtained that: (1) the objective conditions of mathematics learning of elementary students in Central Aceh Regency as follows. a) In the learning process the teacher has not linked mathematics with the local character and potential of the area. b) The mathematics handbook used today has not linked students' personal character. (2) During the learning process of mathematics based on local excellence and the potential character of antusius elementary school students to learn mathematics, the steps of the local superiority-based learning model are (a) the teacher conditions the class, starts with prayer by preparing facilities and infrastructure, doing Apperception of the local potential of central Aceh district b) Presenting contextual problems, Explicitly negotiating, Cooperative intervention, guiding students in groups to discuss contextual issues contained in the LAS. Give students the opportunity to present their model findings through class discussions. c) Guiding students to formulate the results of the discussion while making a summary of the material discussed, Providing material evaluations through giving quizzes or home assignments. The design of elementary school mathematics learning based on locally designed excellence received a good response from all students. 83.74% of students gave a positive response to the local excellence-based learning model. From these results it is expected that the mathematics learning model in the class must be tailored to the needs of students so that the objectives of the learning process can be achieved maximally.